Exploring Sensory Perception and Space Quality in Shaping Rural Cultural Landscape Tourism Experience - Cinthyaningtyas Meytasari; Ikaputra (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: Humans have the most developed senses among living creatures, which shape their perceptions, including spatial quality. In tourism, the tourist experience is the most important, especially in rural cultural landscape. This study examines how sensory elements—such as visual, auditory, tactile, and olfactory stimuli—interact with physical and spatial features, influencing tourists’ emotional responses. The method in this study is qualitative with the research technique being a literature review, focusing on the integration of traditional land use, architecture, and rural cultural landscape, this study explores how sensory factors shape spatial perception. The aim is to understand the importance of sensory experiences in enhancing space quality, thereby enhancing tourists’ experiences in rural cultural landscape. This study ultimately aims to offer insights into maintaining the integrity of these landscapes through sustainable tourism management that prioritizes sensory and space quality. Keywords: Sensory perception, rural cultural landscape, space quality. Abstrak: Manusia memiliki indera yang paling berkembang di antara makhluk hidup, yang membentuk persepsi mereka, termasuk kualitas ruang. Dalam pariwisata, pengalaman wisata adalah yang terpenting, terutama di lanskap budaya pedesaan. Studi ini meneliti bagaimana elemen sensori—seperti rangsangan visual, pendengaran, sentuhan, dan penciuman—berinteraksi dengan fitur fisik dan ruang, yang memengaruhi respon emosional wisatawan. Metode dalam penelitian ini adalah kualitatif dengan teknik penelitian adalah studi literatur, yang berfokus pada integrasi penggunaan lahan tradisional, arsitektur, dan lanskap budaya pedesaan, penelitian ini mengeksplorasi bagaimana faktor sensori membentuk persepsi ruang. Tujuannya adalah untuk memahami pentingnya pengalaman sensori dalam meningkatkan kualitas ruang, sehingga meningkatkan pengalaman wisatawan di lanskap budaya pedesaan. Studi ini pada akhirnya bertujuan untuk menawarkan wawasan dalam menjaga integritas lanskap ini melalui manajemen pariwisata berkelanjutan yang memprioritaskan kualitas sensori dan ruang. Kata Kunci: persepsi sensori, lanskap budaya pedesaan, kualitas ruang. Keywords: Sensory perception, rural cultural landscape, space quality.